1975
DOI: 10.1016/0029-5493(75)90089-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the wall pressure fluctuations in channel flows

Abstract: Numerically simulated turbulent pressure fields in a plane channel and an annulus with a 5 : 1 ratio of radii are used to evaluate the spatial structure of pressure fluctuations at the walls. Wall-pressure correlation functions in the axial and azimuthal directions, spectra, correlation functions and angular correlations of the forces acting on the cylinders of the annulus are considered. It is found that no correlation exists between the pressure values at two points which are diametrically opposed to each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Although there are still large statistical fluctuations we see that the correlation length of the axial velocity fluctuation is about five times that of the other velocity fluctuations. Corresponding results have been found for the annulus [19,21].…”
Section: Numerical Verification Of the Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…Although there are still large statistical fluctuations we see that the correlation length of the axial velocity fluctuation is about five times that of the other velocity fluctuations. Corresponding results have been found for the annulus [19,21].…”
Section: Numerical Verification Of the Methodssupporting
confidence: 80%
“…They showed that some of the empirical "constants" used in simple turbulence models are dependent of the cross-stream position. In [21] it has been shown that the present method can be used to calculate wall-pressure correlation functions and the resultant forces acting on the inner cylinder of the annulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even for homogeneous turbulence, the validity of this model has been questioned (Schumann 1975) and the magnitude of the empirical constant c in it is very uncertain. Values between 0.5 (Daly 1974) and 8 (Lumley & Khajeh-Nouri 1974) have been used even in the more recent literature, mainly because of a gap in experimental data.…”
Section: U Schumann and G S Pattersonmentioning
confidence: 99%